Investigations of surface morphology and microrelief of GaAs single crystals by complementary methods - Zymierska, D.; Auleytner, J.; Dmitruk, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The paper presents the study of morphology and roughness of (100) surfaces of GaAs single crystals grown by the Czochralski method. The surfaces were prepared in a different way: mechanical polishing, chemomechanical polishing, mechanical grinding, wet polishing etching, anisotropic etching. The X-ray grazing incidence reflectivity, atomic force microscopy, scanning tunneling microscopy, optical specular reflection, and profilometric methods were complementary used. The application of these methods allowed to reveal the details of differences in the surface morphology varied with the way of its preparation.